The spread and fauna of orthopterans (Insecta: Orthoptera) in Namangan Region, Uzbekistan - A. A. NURJANOV; M. J. MEDETOV; M. Q. BEGJANOV; B. R. KHOLMATOV; S. A. KHALILLAYEV; F. A. GAPPAROV; F. A. NURJONOV; N. K. TUFLIYEV; M. Y. RADJAFOV (Society for Indonesian Biodiversity, 2024)
Abstract. Nurjanov AA, Medetov MJ, Begjanov MQ, Kholmatov BR, Khalillayev SA, Gapparov FA, Nurjonov FA, Tufliyev NK, Radjafov MY. 2024. The spread and fauna of orthopterans (Insecta: Orthoptera) in Namangan Region, Uzbekistan. Biodiversitas 25: 2619-2628. The Namangan Region, which makes up one-third of the Fergana Valley, is separated from other regions of Uzbekistan by the Kurama and Chatkal mountain ranges. Because of this, the region's fauna differs from the central, northern, and southern areas. During the research (2018-2023), data on the biological diversity, features of inter-landscape distribution, density, and number of orthopterans identified from natural and agrolandscapes of Namangan Region has been analyzed. Samples were collected from 48 coordinates. The results recorded 65 species and subspecies belonging to 8 families, 12 subfamilies, and 46 genera. Furthermore, 38 species (59.4%) of orthopterans found in the territories of Namangan Region are distributed in different agro landscapes, 29 species (45.3%) in hills, and 44 species (68.7%) in mountains. Based on a comparison of species diversity between landscapes using the Jaccard method, it was discovered that there was a 70% difference between species of agrolandscapes (wheat and cotton field) and mountain, a 65% difference between species of mountain and hills, and a 64% difference between species of hills and agrocenosis. In the analysis of species distribution based on density, the following species ranges were found to exist: 8 species are classified as extremely rare, 38 species are classified as constantly distributed, 16 species are classified as common, and 3 species are classified as swarming species. Based on the information obtained from the experiments, it is recommended to add the extremely rare species to the list of unique species and to carry out the control measures against swarming species.